Fourier Analysis of Scanning Laser Polarimetry Measurements with Variable Corneal Compensation in Glaucoma - Medeiros, Felipe A; Zangwill, Linda M; Bowd, Christopher; Bernd, Antje S; Weinreb, Robert N (Investigative ophthalmology & visual science, 2003)
To apply Fourier analysis to the retinal nerve fiber layer (RNFL) thickness measurements obtained with scanning laser polarimetry (SLP), by using variable corneal compensation, and to evaluate the ability of this method to discriminate glaucomatous from normal eyes. The study included one eye each of 55 patients with glaucoma and 52 healthy subjects. RNFL thickness measurements were obtained with a modified commercial scanning laser polarimeter (GDx Nerve Fiber Analyzer; Laser Diagnostic Technologies, Inc., San Diego, CA) so that corneal birefringence could be corrected on a subject-specific variable basis. The shape of the RNFL thickness double-hump pattern was analyzed by Fourier analysis of polarimetry data. Fourier coefficients and GDx parameters were compared between the two groups. A linear discriminant function was developed to identify and combine the most useful Fourier coefficients to separate the two groups. Receiver operating characteristic (ROC) curves were obtained for each measurement, and sensitivity values (at fixed specificities) were calculated. The Fourier-based linear discriminant function (LDF Fourier) resulted in a sensitivity of 84% for a specificity set at 92%. For similar specificity, the GDx software-provided parameters had sensitivities ranging from 24% to 69%. The area under ROC curve for the LDF Fourier was 0.949, significantly larger than the ROC curve area for the single best GDx software-provided parameter, superior average (0.870). The combination of Fourier RNFL thickness measures in an LDF, obtained using SLP with variable corneal compensation, improved the ability to discriminate glaucomatous from healthy eyes, compared with the GDx software-provided parameters.